2010
DOI: 10.1530/rep-10-0223
|View full text |Cite
|
Sign up to set email alerts
|

The Aurora kinase inhibitor ZM447439 accelerates first meiosis in mouse oocytes by overriding the spindle assembly checkpoint

Abstract: Previous studies have established that when maturing mouse oocytes are continuously incubated with the Aurora inhibitor ZM447439, meiotic maturation is blocked. In this study, we observe that by altering the time of addition of the inhibitor, oocyte maturation can actually be accelerated by 1 h as measured by the timing of polar body extrusion. ZM447439 also had the ability to overcome a spindle assembly checkpoint (SAC) arrest caused by nocodazole and so rescue polar body extrusion. Consistent with the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 65 publications
(96 reference statements)
11
48
0
Order By: Relevance
“…Indeed, this repair may be very common in mouse oocytes, given that three rounds of microtubule error correction have been calculated to occur for each bivalent, measured from the time of NEB until polar body extrusion (Kitajima et al, 2011). It is likely, but remains to be firmly established, that Aurora kinases play a part in this process, as they do in mitosis, by destabilizing erroneous attachment that fail to generate adequate tension across the kinetochores (Lane et al, 2010;Liu et al, 2009;Welburn et al, 2010;Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this repair may be very common in mouse oocytes, given that three rounds of microtubule error correction have been calculated to occur for each bivalent, measured from the time of NEB until polar body extrusion (Kitajima et al, 2011). It is likely, but remains to be firmly established, that Aurora kinases play a part in this process, as they do in mitosis, by destabilizing erroneous attachment that fail to generate adequate tension across the kinetochores (Lane et al, 2010;Liu et al, 2009;Welburn et al, 2010;Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…S2B). 40 Despite the potential of reduced SAC activity being present in aged oocytes, it seemed unlikely that the SAC was actually nonfunctional, because there was no increase in aneuploidy with age ( Fig. 1B) to a similar level achieved following loss of individual SAC proteins, 15,17,42 and the duration of MI was not shortened (Fig.…”
Section: Aged Oocytes Have a Reduced Ability To Arrest With Low-dose mentioning
confidence: 95%
“…Aurora C is a substitute of Aurora B during meiosis, [34][35][36][37] and its active form pAurora C is thought to be involved in destabilizing erroneous KT-MT attachment, as such contributing to the fidelity of bivalent division. 34,[38][39][40] One further reason for examining Mad2 is that previous studies have shown that levels of this transcript, like those of other SAC components, are lower in oocytes of both aged mice and humans. 24,25 However, there appears to be no aging defect in SAC activity, 7,28 as measured either by the length of MI, which would be predicted to be shorter in a situation of reduced SAC, or in the ability to arrest in response to a nocodazole challenge.…”
Section: C57bl6/j Oocytes Have Cohesion Loss But No Change In Sgo2 Wimentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetochore is thus both the platform on which the SAC is launched and the tether through which successful poleward PRIMER Development 140 (18) Lane et al, 2010) The acceleration of meiosis I is measured relative to controls; the aneuploidy rate is the absolute level achieved following inhibition of the SAC component (this is usually on background aneuploidy rate of <10%). PRIMER Development 140 (18) chromosome movements are made.…”
Section: The Slow Pace Of Meiosis I Gives Time To Achieve Biorientationmentioning
confidence: 99%